Integrating Knowledge and Democracy for Practical Reform to Overcome Political Crisis in Bangladesh - Mohammad Eisa Ruhullah; Thameem Ushama; Nurul Ain binti Norman (Khazanah Sosial, 2024)
It is crucial to integrate knowledge and democracy into Bangladesh's government to establish a fair and effective system for future leaders. Let us implement this new system to ensure our government serves citizens' needs fairly and justly. This research paper proposes a new method for selecting administrative and state councils at different levels of government based on the Integration/Islamization of Knowledge and Democracy. The study includes interviews with political leaders and experts from Bangladesh and extensive research on politics in the country. The theories involved in this research are from Prof. Emeritus Dato' Dr. Abdulhamid Abusulayman, Profesor Emeritus Tan Sri Dr. Mohd. Kamal bin Hassan, Prof. Dr. Ibrahim Mohamed Zein, and former colleagues and students of al-Faruqi and al-Attas. The two pathways to introduce IoK and modern democracy in Bangladesh and other states with political crises are: 1) Education reform to emphasize interdisciplinary learning, practical applications, and critical thinking, and 2) Government support for policies and funding to promote IoK initiatives, collaboration, and evaluations. Thus, the Integrated Knowledge of Federal Democracy System (IKOFDS) is a proposed governmental structure that aims to empower citizens, enhance governance efficiency, and foster collaborative decision-making. By combining Federalism with the Integration of Knowledge (IoK) and a robust democratic method, the (IKOFDS) seeks to create a balanced and responsive governance model that capitalizes on the strengths of Federalism, knowledge integration, and democratic principles.